Scope and Limitations of γ-Valerolactone (GVL) as a Green Solvent to be Used with Base for Fmoc Removal in Solid Phase Peptide Synthesis - Ashish Kumar (Molecules, 2019)
GVL is a green solvent used in Fmoc-based solid-phase peptide synthesis. It is susceptible to ring opening in the presence of bases such as piperidines, which are used to remove the Fmoc protecting group. Here we studied the formation of the corresponding acyl piperidides by time-dependent monitoring using NMR. The results, corroborated by theoretical calculations, indicate that a solution of piperidines in GVL should be prepared daily for a better Fmoc removal.